Sportorthopädie - Stroehlein JK; van den Bongard F; Barthel T; Reinsberger C (Deutsche Zeitschrift für Sportmedizin)
Background: There is some evidence that regular physical activity has protective effects on cognitive functions in elderly people. The optimal dose of physical activity remains to be elucidated. We conducted a systematic literature research to detect a dose-response-relationship with quantitative measures between physical activity and cognitive performance.Method: We searched PubMed and Ovid for randomized controlled trials. Intensity and total numberof minutes of exercise per week were converted into metabolic equivalent (MET) values per week. Standardized Mean Differences were calculated to determine the effect of the physical intervention on executive functions, attention, processing speed, verbal memory, short- and long-term memory. Methodological quality was assessed by risk of bias with the Cochrane Collaboration tool.Results: 13 studies were analyzed. Eight studies reached two and three points in the quality assessment, five studies reached between four and six points. Low, moderate and high MET/week values were related to marginal, small, medium and high effect sizes for each health status. Indications were found for a linear dose-response relationship between executive functions and MET/week for the MCI population, but not for healthy elderly and AD patients. Conclusion: A dose-response-relationship superior to other intensities was not found for any group. Consensus on cognitive outcomes and the exploration of the effects of different types of exercise in healthy elderly, MCI- and AD-patients might help to elucidate the optimal dose of physical activity on age- and AD-affected cognitive functions.KEY WORDS: Dose-Response-Relationship, Cognitive Performance, Physical Activity, Metabolic Equivalent, Dementia